Biomarkers of HPV in Head and Neck Squamous Cell Carcinoma - Liang, Caihua (2012)
Human papillomavirus (HPV) is an accepted cause of head and neck squamous cell carcinoma (HNSCC) and patients with HPV-associated HNSCC have a favorable prognosis. Currently there is no general guidance on the most appropriate biomarkers for clinical assessment of HPV in these malignancies. We compared PCR-based and serological HPV assays, as well as p16 immunohistochemistry, individually and in combination in a single population-based study to assess their associations with overall survival among HNSCC patients, and thus their potential value as biomarkers. HPV16 serology was determined for 488 patients, immunohistochemical detection of p16 expression in tumors was performed in a subset of 233 cases, and PCR-based methods to assess the presence of HPV16 DNA in a subset of 179 cases’ tumors. Considering each biomarker individually in the subset of patients studied for all endpoints, seropositivity for the E6 and E7 proteins was significantly associated with enhanced all-cause survival in oropharyngeal disease (HR(E6/E7+) =0.1, 95%CI=0.02–0.3). Neither the presence of HPV16 DNA or p16 immunostaining was associated with significant enhanced overall survival in oropharyngeal disease ( HR(DNA)=0.9, 95% CI-0.3–2.9; HR(p16)=0.3, 95%CI=0.1–1.1). However, the combination of HPV positive DNA and E6 or E7 serology was associated with enhanced overall survival in oropharyngeal disease (HR(DNA +/E6/E7+)=0.1, 95%CI=0.02–1.0), while E6/E7 seronegative patients with evidence of HPV in tumor DNA did not show any evidence of favorable survival (HR(DNA+/E6−/E7−)=3.4, 95%CI = 0.6–18.1). Further, patients with p16 staining and E6 or E7 seropositivity had favorable survival from oropharyngeal disease (HR(p16+/E6/E7+)=0.1, 95%CI=0.02–0.4), while patients who were p16 positive and E6/E7 seronegative had significantly increased hazard of all causes of death (HR(p16+/E6−/E7−)=3.1, 95%CI=1.2–7.7). A stronger association of HPV presence with prognosis (assessed by all-cause survival) is observed when "HPV-associated" HNSCC is defined using tumor status (HPV DNA status or P16) and HPV E6/E7 serology in combination rather using tumor HPV status alone.